2022
DOI: 10.1007/s40242-022-2186-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional Xeno Nucleic Acids for Biomedical Application

Abstract: Functional nucleic acids(FNAs) refer to a type of oligonucleotides with functions over the traditional genetic roles of nucleic acids, which have been widely applied in screening, sensing and imaging fields. However, the potential application of FNAs in biomedical field is still restricted by the unsatisfactory stability, biocompatibility, biodistribution and immunity of natural nucleic acids(DNA/RNA). Xeno nucleic acids(XNAs) are a kind of nucleic acid analogues with chemically modified sugar groups that poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Progress has been made in the synthesis of unnatural nucleotide building blocks and in polymerase engineering, enabling the enzymatic generation of artificial nucleic acids. However, the vast majority of enzymatically prepared artificial nucleic acids typically only involve a chemical alteration in one part of their tripartite structure, composed of the phosphodiester backbone, a sugar moiety, and a nucleobase. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress has been made in the synthesis of unnatural nucleotide building blocks and in polymerase engineering, enabling the enzymatic generation of artificial nucleic acids. However, the vast majority of enzymatically prepared artificial nucleic acids typically only involve a chemical alteration in one part of their tripartite structure, composed of the phosphodiester backbone, a sugar moiety, and a nucleobase. , …”
Section: Introductionmentioning
confidence: 99%
“…However, the vast majority of enzymatically prepared artificial nucleic acids typically only involve a chemical alteration in one part of their tripartite structure, composed of the phosphodiester backbone, a sugar moiety, and a nucleobase. 9,14 One prominent sugar-modified nucleic acid that has been thoroughly studied with a particular focus on additional modifications to its xeno nucleic acid (XNA) structure, encompassing alterations in the phosphodiester backbone or the nucleobase moiety, is threofuranosyl-based nucleic acid (TNA). 15−18 TNA was first proposed as a progenitor of RNA by Eschenmoser.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A deep and comprehensive analysis of new classes of nucleic acids was undertaken by Anosova et al [1], who suggested the possibility of storing some of the cell's genetic information on more inert carriers than natural nucleic acids. Since then, a number of excellent reviews have appeared [2][3][4][5][6][7][8][9], alongside some especially exciting ones devoted to the prospects of creating orthogonal replication competent systems or xeno-lives [10][11][12][13] which include completely different two-base strands with dynamic covalent interactions between boronic acids (BAs) and catechols (CAs) as synthetic nucleobase analogs [14].…”
Section: Introductionmentioning
confidence: 99%